1981
DOI: 10.2307/1941520
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Structure of Herbivorous Insect Communities in a Salt Marsh

Abstract: Factors regulating the numbers and species of herbivorous insects in a salt marsh were experimentally investigated by chronic fertilization of plots. All biweekly nutrient enrichments (urea or three dosages of a mixed fertilizer) resulted in increased grass standing crop in low and high marsh habitats. Plant nitrogen content increased only in those plots receiving the two highest levels of mixed fertilizer. Grass responses were most rapid where the highest nutrient load was applied.In all plots, fertilization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 43 publications
(73 reference statements)
4
117
0
Order By: Relevance
“…However, the estimates of species richness from individual-based rarefaction did not increase with fertilization for any trophic group. Numerous studies have examined the diversity of herbivorous or other arthropods in response to fertilization, but generalizations have been elusive (e.g., Hurd and Wolf 1974;Kirchner 1977;Kajak 1981;Vince et al 1981;Prestidge 1982;Strauss 1987;Sedlacek et al 1988;Siemann 1998;Haddad et al 2000). However, several of these studies observed higher abundance of sap-sucking Auchenorryncha and other herbivorous groups, but decreasing evenness and diversity as a small number of species emerged as dominant (Prestidge 1982;Sedlacek et al 1988;Haddad et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, the estimates of species richness from individual-based rarefaction did not increase with fertilization for any trophic group. Numerous studies have examined the diversity of herbivorous or other arthropods in response to fertilization, but generalizations have been elusive (e.g., Hurd and Wolf 1974;Kirchner 1977;Kajak 1981;Vince et al 1981;Prestidge 1982;Strauss 1987;Sedlacek et al 1988;Siemann 1998;Haddad et al 2000). However, several of these studies observed higher abundance of sap-sucking Auchenorryncha and other herbivorous groups, but decreasing evenness and diversity as a small number of species emerged as dominant (Prestidge 1982;Sedlacek et al 1988;Haddad et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen additions likely do not only affect primary producers, but also flow through the food web to affect other trophic levels (Vince et al 1981, Tober et al 1996, Rosemond et al 2001. Although almost all trophic levels are potentially limited by nitrogen (Sterner and Elser 2002), whether particular populations actually respond to added nitrogen in the field depends on what additional factors constrain their response.…”
Section: Introductionmentioning
confidence: 99%
“…Although almost all trophic levels are potentially limited by nitrogen (Sterner and Elser 2002), whether particular populations actually respond to added nitrogen in the field depends on what additional factors constrain their response. For example, responses of salt marsh herbivores to nitrogen, although generally positive, have been suggested to be limited by competition, predation or life-cycle constraints (Vince et al 1981, Stiling et al 1991, Moon and Stiling 2002. Similar constraints might limit the responses of decomposers or detritivores to nutrient additions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the number of 332 herbivore insects increased when the nutritional quality of salt marsh plants improved as 333 a result of higher nutrient loading increased (Vince et al 1981). All of this evidence 334 suggests that we might expect increased arthropod availability for birds with an increase 335 of nutrient loadings to marshes.…”
Section: Rush-tyrant (Tachuris Rubrigastra) Wren-like Rushbird (Phlementioning
confidence: 99%